Estimating yield stability by nonparametric stability analysis in maize (Zea mays L.). - Dehghani, Hamid (Plant Breeding and Seed Science, 2008)
Assessment of the stability of a genotype to different environments is useful for recommending genotypes for known conditions of cultivation and should be a requirement in plant breeding programs. Nonparametric models do not require parametric assumptions and are good alternatives for parametric measurements to genotypes × environments (GE) interaction study.Twelve maize (Zea mays L.) genotypes were tested at eleven locations in for two years (22 environments). The experiments involved a randomized complete block design in which twelve nonparametric procedures were used to analyze genotype stability. Results of nonparametric tests of GE interaction and combined ANOVA showed there were both noncrossover and crossover GE interaction...